Economic development and institutions – Mozambique at a fork in the road: an institutional diagnostic: Synthesis and policy recommendations - Cruz, Antonio S; Ferreira, Ines A; Flentø, Johnny; Tarp, Finn (Economic development and institutions, 2020)
We now proceed to bringing together the different elements of previous chapters with the aim of presenting the essence of this country study of Mozambique. In the next section, we take stock and revisit our points of departure from Chapters 2 and 3. This background work culminated in the identification of nine thematic areas, subsequently subjected to individual in-depth studies in Chapters 4–12. We outline the core findings from these studies, and present our integrated analysis of key institutional weaknesses. Next, we go a decisive step further, and analyse and discuss their proximate causes and deep factors. We end with a series of ideas for reform, as an input to national reflection, debate, and action.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; ⛔ No DOI found

Towards Social, Economic and Inclusive Policies for People with Disability in Mozambique - Khadiagala, Gilbert M.; Manhique, Jorge R. (WFD - Moçambique, 2019)
The inclusion of persons with disabilities is an essential element of a strong democracy and a just society. Persons with disabilities (PWDs) being included means that they have a full and equal opportunity to participate in society and in political decision-making processes, to develop their capacities, and to contribute to national progress Like everywhere, persons with disabilities in Mozambique face physical, social, economic and/or environmental barriers to participation. For example, 17 percent of persons with disabilities in Mozambique have been refused entry into a school or preschool because of their disability. Prior to its ratification of the International Convention on the Rights of People with Disability (ICCPD), which protects and promotes the rights and dignity of persons with disabilities, Mozambique had already pioneered progressive measures to promote the inclusion of persons with disability through specific principles in the Constitution of the Republic and the development of multisectoral plans on disability. Furthermore, the Mozambican Government proposed a new set of commitments that were presented at the London Summit in July 2018, reaffirming its adherence to the International Convention on the Rights of People with Disability. The Mozambican Minister for Gender, Children and Social Action, Her Excellency Cidália Manuel Chaúque Oliveira, today spoke at an event on 18th December to launch the study, ‘Towards Social, Economic and Inclusive Policies for People with Disability in Mozambique.’ The study is the result of consultations with people with disabilities of different types and other stakeholders working to promote the rights of persons with disabilities (PWDs) in the Nampula, Beira and Maputo regions of Mozambique. The consulations aimed to find out about the socio-economic and political situations of PWDs and the barriers they face, as well as propose solutions to those problems. The consultation is part of the effort to establish a National Agenda for greater social, economic and political inclusion of PWDs in Mozambique. The study identifies the opportunities for, progress made, obstacles to, and consensus on national policies and strategies. It articulates a ways forward for building an inclusive society and achieving social justice. The study contibutes to Mozambique’s efforts work effectively towards national and international commitments to inclusive development. The study was undertaken as part of the Commonwealth Partnership for Democracy (CP4D) programme. It was carried out by WFD Mozambique in partnership with the Mozambican Association of People with Disability (ADEMO), the Mozambican Forum of Associations for People with Disability (FAMOD), and the Assembly of the Republic of Mozambique, in collaboration with the Ministry of Gender, Children and Social Action and with the technical advice of the Centre for Human Rights of the University of Pretoria in South Africa.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Political economy of decentralisation in Mozambique: dynamics, outcomes, challenges - Weimer, Bernhard; Carrilho, João (Instituto de Estudos Sociais e Económicos (IESE), 2017)
The book approaches the topic in a multidisciplinary and multisectoral manner and considers different viewpoints, including political, institutional and that of public administration, finances and society. The authors look at the relationship between decentralisation and democratisation, a subject debated in political sciences: Does decentralisation correspond to a more advanced level of democracy? Regarding its life as a democracy, Moçambique is still a young country and the book provides a clear picture of the history of decentralisation from 1992 to today. Its basic argument is that the political class which has been in power since Independence systematically sought to limit or, on occasion, halt decentralisation. Is this thesis acceptable? And is it sustained by the evidence which the book produces? In general, it is possible to reply affirmatively to both questions. The fact that the government has increased the number of districts, some of which perfectly overlap with the territory of the respective municipalities, is offered as proof to verify the central proposition. Furthermore, in the context of today’s political discourse around the future, the government’s reservation in increasing the number of municipalities constitutes one of countless demonstrations of how cautious the government’s approach to this subject is.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; governance / governação; government policy / politica governamental

Social Movements, Agrarian Change and the Contestation of ProSAVANA in Mozambique and Brazil - Shankland, Alex; Gonçalves, Euclides; Favareto, Arilson (Future Agricultures Working 137, 2016)
In this study, we set out to examine three interrelated questions: To what extent has Brazilian cooperation in the agriculture sector contributed to agrarian transformation in Mozambique? How has Mozambican civil society, and in particular the União Nacional dos Camponeses (UNAC, National Peasants’ Union), responded to the prospect of Brazilian agribusiness investments in the Nacala Corridor? And what effects has BrazilianMozambican agricultural development cooperation had on the existing relations among Brazilian and Mozambican rural social movements, in particular UNAC and Brazil’s Movimento dos Trabalhadores Sem Terra (MST, Landless Rural Workers’ Movement) and Movimento dos Pequenos Agricultores (MPA, Movement of Small Farmers), as well as between these movements and other civil society groups?
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; Northern PEA; agriculture / agricultura; government policy / politica governamental; south-south cooperation / cooperação sul-sul

Transforming Cash Transfers: Beneficiary and community perspectives of the Basic Social Subsidy Programme in Mozambique - Selvester, Kerry; Fidalgo, Lourdes; Tambo, Neila (Overseas Development Institute (ODI), 2012)
The increasing recognition that social protection programmes in developing countries can play an important role in inclusive and transformative development is welcomed by analysts as a step towards supporting extremely poor households in these countries. In Mozambique, the national cash transfer programme, the Basic Social Subsidy Programme (Programa de Subsídio Social Básico or PSSB), which began in 1992, provides a relatively low value of 130 MTn (approx. $4.5) to 380 MTn (approx. $13), narrowly targeted transfer to nearly 300,000 extremely vulnerable households. The programme has clear political commitment to sustainability, using state funds. The PSSB is not an isolated intervention; rather, it is part of a broader social protection platform that includes providing support to households that temporarily find themselves unable to overcome a specific shock or event, along with social assistance delivered through the health and education sectors. The social protection system in Mozambique is in the process of being reformed and modernised, which should result in a more transparent and accountable system. One of the key reforms involves the development of a management information system (MIS) that will provide an integrated technical platform for the management of the social assistance programmes. The key research objectives of this study are:  to explore the views, experiences and perceptions of cash transfer programme beneficiaries and other community members (non-beneficiaries) in order to ensure that they are better reflected in policy and programming  to gather perceptions and experiences from programme implementers  to provide examples of best practice on how to involve beneficiaries and communities in participatory monitoring and evaluation (M&E) of cash transfer programmes  to build the capacity of national researchers in qualitative and participatory data collection and analysis. The research report presents background information on cash transfers in Mozambique in order to frame the detailed qualitative and participative study conducted in two districts in the southern province of Gaza, Chokwe and Chibuto. The research focuses on people with disabilities who receive the cash transfer. Currently, of the 286,176 people with disabilities living in poverty), less than 14,000 households with disabled members are receiving the government cash transfer. The fieldwork for the research was preceded by a demand generation consultation (DGC) exercise that provided valuable insights into stakeholders’ concerns in terms of the delivery and impact of the PSSB on beneficiaries’ lives, particularly on households headed by people with disabilities. Stakeholders were concerned that the research examined the extent to which beneficiaries are aware of their rights, the procedures and regulations of the PSSB, and whether there was any transparency, at local level, in the selection of beneficiaries. The research team used a wide variety of qualitative data collection tools with a view to collecting in-depth information about the impact of the cash transfer on beneficiaries’ lives and perceptions of all stakeholders (including beneficiaries) about the extent to which the PSSB was a transparent and accountable mechanism. All of the fieldwork tools were pre-tested in the peri-urban area of BairroAreoporto, Maputo city. There was unanimous agreement among all stakeholders interviewed that the value of the transfer was too low to be considered a transformative measure and is rather perceived as a minimum welfare payment to reduce the possibility of vulnerable households becoming destitute. Advocacy is needed to increase the real value of the transfer in order to strengthen resilience of the most vulnerable households. The Mozambique Government’s implementing agency, the National Institute for Social Action (INAS), recognises that the fiscal space for the programme is still relatively constrained, whic vi means there is a lack of sustainable financial capacity to address the problems of all vulnerable groups that fall within its mandate. Improving beneficiary management and outsourcing payments to private sector providers are the main pillars of change currently proposed by INAS to begin to address this issue. Our research highlighted the need for coordinated and harmonised support to the sector by development cooperation partners to ensure that reform efforts build an integrated social protection system rather than creating unsustainable ad hoc programmes that satisfy the short-term goals of individual donor agencies. The research clearly identified how little information was available about the PSSB at all levels of the system, leading to a lack of transparency, and ultimately a lack of accountability to beneficiaries. The report recommends that there is a need for a comprehensive communication and education strategy to reach all the stakeholders, including the use of media (particularly radio), capacity-building and refresher training for staff and community liaison agents, and the production and dissemination of simple printed materials describing key elements of the programme. There was a clear indication in the research that people with disabilities are under-represented in the programme, and more importantly do not feel that they have a right to complain about any aspects of it. A lack of understanding (on the part of the implementing agency and staff) about the needs of the programme’s target groups has led to people feeling that the cash transfer was solely a pension provided to older people, those who are unable to work and those who are chronically poor. Physical access to the people who fill in the application forms1 was considered less of a barrier than feelings of lack of entitlement by extremely poor people living with a disability. Making targeting mechanisms and criteria more transparent (easily understood) through clear and well-disseminated information would reduce the bias against applicants with disabilities. Our research also found that demand for accountability from beneficiaries was low, as they generally have few expectations of the government institutions or other agencies that provide assistance ‘system’; creating a demand for transparency is a challenge that will require considerable political will, information campaigns and engagement of multiple stakeholders. With the aforementioned modernisation of the social protection system, there are openings to improve transparency that could lead to greater accountability at all levels. These include the development of an effective grievance system to increase and improve communication between beneficiaries and INAS, which, over time, could create a sense of mutual accountability and trust. In addition, there were calls from INAS officials, local leaders and beneficiaries for independent, participatory monitoring of the programme. The recently formed Civil Society Platform for Social Protection is designing a community-based monitoring system for social assistance programmes, which will be piloted in 2013. Government actors as well as non-government actors in Mozambique recognise that there is a lack of structured and institutionalised coordination and collaboration between entities working in the social protection sector. This leads to duplication of efforts in some areas and glaring service gaps in others. Mechanisms need to be set up at local level to bring these entities together to share information and establish simple working guidelines for collaboration. Each district should establish locally specific mechanisms based on guiding principles of openness, collaboration and transparency of action. There are deep concerns about the human resource capacity of INAS to fulfil its wide mandate of not only providing social assistance transfers but moving towards case management of beneficiaries and the delivery of a transparent and accountable social protection system. Throughout the report, the voice of programme beneficiaries is clearly presented, indicating above all the urgency required to deliver more effective and efficient social protection programmes that will give the most disenfranchised people an opportunity to participate socially and economically in society.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; social protection / proteção social

PPFD/PRODER Joint Review and Strategy Proposal for the National PPFD Program Architecture - Final report - Ministry of Planning and Development - Mozambique (MÉTIER, Consultoria e Desenvolvimento, Lda, 2006)
The present report integrates the main conclusions of the three PPFD projects evaluation: PPFDNorth, PPFD-Centre and PRODER, establishing the articulation with the evolution of the political and administrative evolution and relevant for the decentralization process. Based on this analysis the report proposes the architecture of a single National PPFD Program and its main components. This report is based on the main conclusions of an extensive field work covering various provinces and districts and of the various workshops with participation of representatives of the Government at different levels, of the partners and national and international staff from the projects. It constitutes an important basis for the work of the commissions created to start the program formulations. This final report is complemented by other four partial reports: Evaluation report of the PPFD North; Evaluation report of the PPFD Centre; Evaluation report of the PRODER; and Phases 2 and 3 Report: Strategy for a single national PPFD
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; government policy / politica governamental